Analisis Faktor-Faktor Yang Mempengaruhi Manajemen Laba Pada Perusahaan Manufaktur Subsektor Farmasi Yang Terdaftar Di BEI - Ayu Ceria Dewi Lubis; Junita Putri Rajana Harahap (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This study aims to analyze and determine the effect of profitability, managerial ownership and leverage on earnings management in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange. In this study, the sampling technique used saturated sampling, in which the entire population was sampled. The number of samples in this study was 10 pharmaceutical sub-sector companies, each consisting of 4 years of financial statements, so that the total sample consisted of 40 samples. The data analysis tool in this study used multiple linear regression analysis which was previously tested for classical assumptions so that the results obtained were not biased. Based on the results of the partial test (t-test) in this study, it states that: 1) profitability affects earnings management in pharmaceutical sub-sector manufacturing companies. 2) managerial ownership does not affect earnings management in pharmaceutical sub-sector manufacturing companies. 3) Leverage has a significant effect on earnings management in pharmaceutical sub-sector manufacturing companies. And simultaneously profitability, managerial ownership and leverage affect earnings management.